Physicochemical Investigations of Th(IV) and UO2(VI) Complexes with New Schiff Bases Along with their Toxic Effects - Sonal Agnihotri; Kishor Arora (E-Journal of Chemistry)
Schiff bases were obtained using p-trimethoxy benzaldehyde, p-hydroxyl benzaldehyde and 2-amino pyridine to prepare new complexes of thorium(IV) and dioxouranium(VI) metals by various anions. The synthesized ligands and complexes were analytically studied through spectral studies, elemental analysis conductance measurements along with semi empirical and thermogravimetric methods. The complexes were assigned various coordination numbers ranging from 6-10 on the basis of these studies.